B2B: A Shift from Owning to Sharing? - How Sharing Facilitates new Business-to-Business Relationships between Small and Medium-sized Enterprises - Sebastian Huber; Karina von dem Berge; Simona Burri; Uta Jüttner; Toni Wälfer; Charles Huber; Luca Niederhauser (Marketing Review St.Gallen, 2022)
The sharing economy has witnessed tremendous growth in a multitude of industries around the world. Little B2B sharing, however, can be observed in industry practice, although it provides attractive opportunities for SMEs. Findings from an applied research project suggest some prerequisites for SMEs that want to engage in sharing and offer several tools for implementation.
Keywords: 650